Pengaruh Motivasi Terhadap Penyelesaian Skripsi Mahasiswa Pendidikan Ekonomi Universitas Negeri Padang - Fadly Rudaniel; Dessi Susanti (Universitas Negeri Padang, 2023)
This study aims to determine the impact of motivation on the completion of the thesis of students of economics at the country college of Padang. This research was conducted because many college students in economic education at the Faculty of Economics at Padang Country College had been restricted and had difficulty finishing their very last assignments, so they did not graduate on time. This kind of study is descriptive-associative. The population is economic education college students at the School of Economics, Padang State University, in 2015, 2016, and 2017, and the total sample size is 109 college students. The sampling strategy is probability sampling with proportional stratified random sampling. The data collection techniques in the shape of a questionnaire. Descriptive analysis, necessities analysis, simple regression, F check, determinant coefficient, and the t test are all used in information analysis. The results showed that motivation affected the overall thesis in a significant and pervasive way. shown via the F test value obtained by using an F count of 3.93 with an R square of 0.068 (6.8%) and a tremendous level of 0.000<0.05. And the result of the t-count is greater than the t-table of 2.978>1.982, which means that H0 is rejected and Ha is generally believed or recognized to be valid or correct.